Blue-conversion of organic dyes produces artifacts in multicolor fluorescence imaging. Issue 25 (24th May 2021) - Kim, Do-Hyeon; Chang, Yeonho; Park, Soyeon; Jeong, Min Gyu; Kwon, Yonghoon; Zhou, Kai; Noh, Jungeun; Choi, Yun-Kyu; Hong, Triet Minh; Chang, Young-Tae; Ryu, Sung Ho
Abstract : Blue-conversion, a photooxidative conversion leading to the hypsochromic shift of absorption and emission spectra, occurs in popular organic dyes under conventional laser illumination and produces severe artifacts in multicolor fluorescence imaging. Abstract : Multicolor fluorescence imaging is a powerful tool visualizing the spatiotemporal relationship among biomolecules. Here, we report that commonly employed organic dyes exhibit a blue-conversion phenomenon, which can produce severe multicolor image artifacts leading to false-positive colocalization by invading predefined spectral windows, as demonstrated in the case study using EGFR and Tensin2. These multicolor image artifacts become much critical in localization-based superresolution microscopy as the blue-converted dyes are photoactivatable. We provide a practical guideline for the use of organic dyes for multicolor imaging to prevent artifacts derived by blue-conversion.